Mutational Profile and Potential Molecular Therapeutic Targets of Pheochromocytoma - Ma, Xiaosen; Ling, Chao; Zhao, Meng; Wang, Fen; Cui, Yunying; Wen, Jin; Ji, Zhigang; Zhang, Caili; Chen, Shi; Tong, Anli; Li, Yuxiu (Frontiers in Endocrinology, 2022)
Purpose: Pheochromocytoma/paraganglioma (PCC/PGL; collectively known as PPGL) can be driven by germline and somatic mutations in susceptibility genes. We aimed to investigate the mutation profile and clinical features of pathogenic genes in highly genetically heterogeneous PPGL and to preliminary explore molecular therapeutic targets in PPGL. Methods: We established a panel of 260 genes, including susceptibility genes of PPGL and other important tumorigenic genes to sequence 107 PPGL tissues. Results: Overall, 608 genomic mutations were identified in 107 PPGL tissues. Almost 57% of PPGL tissue samples exhibited pathogenic mutations, and the most frequently mutated gene was SDHB (15/107, 14%). SDHB and HRAS were the most commonly mutated genes in germline-mutated PPGL (25/107, 23%) and nongermline-mutated PPGL (36/107, 34%), respectively. In addition, novel pathogenic mutations were detected in sporadic PPGL. PPGL with mutations in the hypoxia pathway had an earlier onset and higher norepinephrine level than those in the kinase pathway. Receptor tyrosine kinase (RTK; 22%, 24/107), mitogen-activated protein kinase (MAPK; 14%, 15/107), and tyrosine kinase (TK; 2%, 2/107) pathways were the most frequently mutated pathways in PPGL. Conclusion: Our results provided the genetic mutation profile in PPGL tissues. Genetic mutations in PPGL were mainly concentrated in the RTK, TK, and MAPK pathways, suggesting potential molecular therapeutic targets for PPGL.